Depression, anxiety and stress among pharmacy students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (University of Dicle, 2020)
Psychological well-being is an essential factor in the sustainability of prosperous academic performance during undergraduate studies. Pharmacy students are exposed to a wide range of stressors during their study. Severe and continued stressors may affect the mental health in variable degrees and may precipitate depression, anxiety and stress which may affect students’ academic performance, physical health and quality of life. Therefore, this study aimed to assess the prevalence and severity of depression, anxiety and stress symptoms and also to assess the relationship between these symptoms with stressors faced by the students. A sample of 223 students from Kulliyyah (faculty ) of Pharmacy, International Islamic University Malaysia participated in this study. Depression Anxiety, Stress Scale (DASS-21) was used to assess the emotional disturbances by determining the prevalence and severity of depression, anxiety and stress (DAS) symptoms. The sources of stressors were identified by giving the students a list of the most possible source of stressors which were chosen depending on previous studies, and then the severity of stressors and their relationship with these symptoms were assessed. The overall prevalence of depression, anxiety and stress symptoms was 50.7 %, 72.2%, % and 42.2% respectively but it was found that 11.7%, 33.6 % and 11.7% of pharmacy students have clinically significant depression, anxiety and stress respectively. No significant differences between the genders in relation to DAS symptoms. Stressors such as fear of failing, academic overload, fear of unemployment after graduation, exams, and problems in time management were considered the most potent stressors and were significantly associated with DAS symptoms. Symptoms of depression, anxiety and stress are significantly existent among pharmacy students which need to be early detected. Academic related factors can be viewed as sources of stressors that may induce emotional disturbances among the pharmacy students